Prototype Media Pembelajaran Video Tutorial Pada Mata Pelajaran Teknologi Perkantoran di SMK Negeri 4 Surabaya - Novan Hartantyo Aji; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Office Technology is one of the subjects taught at the Vocational High School in the curriculum of 2013. Subject that was taught in Office Technology is the basics of using tools that often used in the offices to make it easier to complete work. The studying media that evolved on this take a look at are tutorials via video getting to know. Video is a technology for sending digital statistics from shifting photographs, whilst an educational is a manner to do some thing, so a video academic is a moving photo which could ship information. The purpose of this observe is to explain the outcomes of the development of learning by way of video academic on office technology subjects at SMK Negeri 4 Surabaya. This form of research is development research. The development version used is the 4D improvement model from Thiagarajan, Semmel, and Sammel which includes the define, layout, develop, and disseminate degrees. This research was achieved best on the design level, no longer until the broaden and disseminate degree. primarily based on the effects of the take a look at, on the degree of defining an evaluation of several matters is used inside the improvement of instructional media is the preliminary analysis, student analysis, project analysis, idea analysis, and specification of studying objectives. After that the layout stage is performed with several levels, specifically media selection and media layout. In designing media, determining media content, recording, modifying is achieved that allows you to produce a video educational layout that may be used by students as a getting to know medium with the intention to achieve an facts related to office generation topics as fundamental competencies in working word processing programs. the tutorial video is divided into separate films that adjusted to the difficulty matterm, to regulate the duration of the video to makes it less complicated for college kids to locate statistics inside the tutorial video related to the fundamental abilties of operating a phrase processing utility.